(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Adenomas of the large intestine, also known as colorectal adenomas, are benign epithelial tumors characterized by dysplastic changes in the intestinal mucosa. They are considered precursors to colorectal carcinoma, making their identification and morphological characterization crucial for early detection and prevention of colorectal cancer (CRC) [1].